2002
DOI: 10.1007/s11663-002-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical behavior of copper molds during thin-slab casting (I): Plant trial and mathematical modeling

Abstract: Three-dimensional (3-D) finite-element thermal-stress models have been developed to predict temperature, distortion, and residual stress in the mold of continuous casters of thin steel slabs, comparing both funnel-shaped and parallel molds. The mold shape and high casting speed leads to higher mold temperatures and shorter mold life than in conventional slab casters. This study investigates heat flux and the effects of mold shape on distortion and cracking of the thin-slab mold. In Part I of this twopart artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 4 publications
1
54
2
Order By: Relevance
“…Heat transfer in funnel moulds has been investigated in only a few previous studies, examining heat flux profiles, 1) mould distortion and cracking, [1][2][3] phenomena in the steel/flux interface, [4][5][6] and fluid flow coupled with solidification heat transfer. 7) Heat flux tends to be higher in thin-slab casting than in conventional billet or slab casting, which is attributed to the higher casting speeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat transfer in funnel moulds has been investigated in only a few previous studies, examining heat flux profiles, 1) mould distortion and cracking, [1][2][3] phenomena in the steel/flux interface, [4][5][6] and fluid flow coupled with solidification heat transfer. 7) Heat flux tends to be higher in thin-slab casting than in conventional billet or slab casting, which is attributed to the higher casting speeds.…”
Section: Introductionmentioning
confidence: 99%
“…7) Heat flux tends to be higher in thin-slab casting than in conventional billet or slab casting, which is attributed to the higher casting speeds. 1) Computational models can reveal insights into mould heat transfer, so long as they have been calibrated with plant data. Recent modelling studies of billet casting, which use thermocouple measurements and inverse heat transfer calculations to determine the heat flux profile, have shown that mould hot-face temperature increases with increasing mould plate thickness and casting speed.…”
Section: Introductionmentioning
confidence: 99%
“…where T is the temperature, ρ, λ and C p are the density, thermal conductivity and specific heat, respectively, which can be obtained in Table 2, and ω is the source of heat [1] , which is 0 in this study. The axes of x, y and z in the coordinate system are parallel to the length, the height and the width of copper plate, respectively, and their coordinate origin is at the midpoint of the symmetry plane in the half copper plate.…”
Section: Heat Transfer Model and Boundary Conditionmentioning
confidence: 99%
“…In order to assess the role of various process parameters impacting mold life, O'Connor and Dantzig developed a finite-element model to calculate the thermo-mechanical state in the mold and casting slab [4] . Thomas and Park et al applied a threedimensional finite-element model to predict temperature, thermal distortion, thermal stress and hot face cracks in a funnel shaped mold for casting thin-slab [1,[5][6][7] . Santillana et al applied a one-dimensional finite-element model to modify the 3D model, and predict temperatures for copper plates with different thicknesses [8,9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation